Enhancement of Public Real-estate Assets and Cultural Heritage Management Plans and Models, Innovative Practices and Tools in Supporting the Local Sustainable Development - Della Spina, Lucia; Calabrò, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The management of cultural heritage and public real-estate assets is one of the most crucial challenges concerning the sustainable use of these resources, involving dynamic methods to stimulate preservation, development, renewal, and transmission to future generations of these essential assets. The contributions presented in this book provide a rich and varied panorama of research experiences and innovative tools, capable of promoting the re-use of cultural heritage in European cities and cultural landscapes, using a circular economy logic as a model of sustainable development. From this point of view, cultural capital becomes the driver of a regeneration process on the local, urban, and metropolitan scales, in which the transversal interconnections between the production cycles of the adaptive re-use of the available heritage, both in the adaptation and in the management phase, configure a circular process of multidimensional production of value. Therefore, future territorial redevelopment projects can base their idea strength on an open system of appropriately selected social attractors, whose enhancement and use have the objective of triggering widespread regeneration effects on the whole territory of influence, receiving inducement and resources to progress.